Tolerance towards gentamicin is a function of nutrient concentration in biofilms of patient-isolated Staphylococcus epidermidis - Ammann, Christoph G. (Folia Microbiol (Praha), 2017)
Staphylococcus epidermidis is a biofilm-forming bacterial strain that can cause major problems as an agent of nosocomial infections. Bacteria in biofilms are shielded from the environment and can survive high doses of antibiotics. We here test the antibiotic susceptibility of Staphylococcus epidermidis to rising gentamicin concentrations in optimal growth conditions as used in routine bacteriology laboratories with low nutrient situations as suggested to be found in clinical situations. We found that gentamicin-resistant Staphylococcus epidermidis biofilms survived in the absence of external nutrient supply in PBS. While addition of gentamicin sulfate significantly reduced the pH value of all used media and solutions, this acidification did not alter survival of bacteria in the biofilm. We found a statistically significant and dose-dependent reduction of survival in low nutrient situations using gentamicin sulfate in three out of four patient isolates of Staphylococcus epidermidis which have been tested to be gentamicin-resistant under optimal growth conditions. Supporting the original profiling, survival in full media under the same antibiotic dosages was not significantly reduced. Our data here show that antibiotic resistance is a function of the provided nutrient concentration. Antibiotic resistance profiling should consider variations in nutrient availability.